Performance of biochar as a catalyst for tar steam reforming: Effect of the porous structure. (1st February 2020) - Buentello-Montoya, David; Zhang, Xiaolei; Li, Jun; Ranade, Vivek; Marques, Simão; Geron, Marco
Graphical abstract: Highlights: The catalytic performance of char can be maintained at high temperatures (e.g. 850 °C). Microporous chars deactivate faster than mesoporous chars. At elevated temperatures activated char and regular char demonstrate similar performance. Simulations showed that mesoporous chars conserve their catalytic activity for over 10 h. Coke in micropores cannot be gasified even at high temperatures (e.g. 850 °C). Abstract: The application of gasification to thermally treat biomass as carbon neutral resources has been constrained by the technical challenges associated with tar formations, which cause operational problems in downstream equipment for syngas processing. Catalysts, such as transition metals, calcined rocks and char, can be used to catalyse tar reforming. Biochars, which are naturally produced during biomass gasification, are particularly attractive as an alternative catalyst due to their catalytic functions, low cost and long endurance. Despite these promising characteristics, adequate knowledge on the relationship between the porous structure of biochar and its deactivation by coking during the steam reforming of tars is not available. In this work, the influence of the porous structure of biochar on its performance across time for reforming tar was investigated in a fixed-bed reactor, over a temperature range from 650 to 850 °C. Regular biochar and physically activated biochar from the same precursor biomass were employed as bed material. The tar samples were the composed mixture of benzene, toluene and naphthalene. Both fresh and spent catalysts were analysed with Brunauer-Emmet-Teller, t-plot, Fourier Transform Infrared and Scanning Electron Microscopy/Energy Dispersive Spectroscopy. Results showed that, while at moderate temperatures of 650 and 750 °C, the activated biochar offered a higher tar conversion but more severe deactivation than that of the regular biochar. At the high temperature of 850 °C, the difference in the catalytic performance between the two chars was negligible, and over 90% of the initial tar species were removed throughout the 3-hour long experiments. At 850 °C, the coke deposited in the meso- and macro-pores of both chars was gasified, leading to a stable catalytic performance of both chars. The results indicated that meso- and macro-porous biochars are resilient and active enough to become a viable option for tar steam reforming.